The Delay in the Licensing of Protozoal Vaccines: A Comparative History - Palatnik-de-Sousa, Clarisa Beatriz; Nico, Dirlei (Frontiers in Immunology, 2020)
Although viruses and bacteria have been known as agents of diseases since 1546, 250 years went by until the first anti-virus and anti-bacterial vaccines were developed (1796 and 1800s). In contrast, Malaria which is a protozoan neglected disease has been known since the 5th century BCE and despite 2,500 years having passed since then, no human vaccine has yet been licensed for Malaria. Additionally, no human modern vaccine is currently licensed against Visceral or Cutaneous leishmaniasis. Vaccination against Malaria evolved from the inoculation of irradiated sporozoites through the bite of Anopheles mosquitoes in 1930’s, which failed to give protection, to the use of controlled human Malaria infection (CHMI) provoked by live sporozoites of Plasmodium falciparum and curtailed with specific chemotherapy, since 1940’s. Although of high efficacy predictive value, CHMI has some ethical limitations and was substituted by the use of injected recombinant vaccines expressing the main antigens of the parasite cycle, which started in 1980. Pre-erythrocytic (PEV), Blood stage (BSV), transmission blocking (TBV), antitoxic (AT) and pregnancy-associated Malaria vaccines are under development. Currently, the RTS´S-PEV vaccine, based on the circumsporozoite protein is the only one that arrived at the Phase III trials stage. In contrast, currently there are four licensed veterinary vaccines against visceral leishmaniasis: Leishmune® (76-80 % VE) and CaniLeish® (68.4 % VE), which give protection against strong endpoints: severe disease and deaths under natural conditions; and, under less severe endpoints (parasitological and PCR positive cases), Leishtec® developed 71.4 % VE in a low infective pressure area but only 35.7 % VE and transient protection, in a high infective pressure area, while Letifend® promoted 72 % VE. A human recombinant vaccine based on the Nucleoside hydrolase of Leishmania (L.) donovani, and the sterol 24-c-methyltransferase (SMT) from L. (L.) infantum has reached the Phase I clinical trial. This review describes the history of vaccine development, and is focused on licensed formulations that have been used in preventive medicine. Special attention has been given to the delay in the development and licensing of human vaccines against Protozoan infections, which show high incidence worldwide and still remain severe threats to Public Health.